Incidence, Molecular Detection, and Partial Nucleotide Sequencing of Some Viruses Causing Fig Mosaic Disease (FMD) on Fig Plants in Egypt. (31st May 2022) - Toima, Neven I.; El-Banna, Om-Hashem M.; Sayed, Ali M.; Youssef, Sahar A.; Shalaby, Ahmed A.
Abstract : Fig mosaic disease (FMD) is a viral disease that poses a significant danger to Egypt's fig-producing economy. During the two growing seasons 2017 and 2018, fig leaves and fruits displaying a variety of symptoms linked with fig mosaic disease (FMD) were collected and differentiated from the most famous fig-growing governorates in Egypt, Mersa Matruh, Ismailia, and Giza. Symptomatic samples were tested for the presence of fig mosaic virus (FMV), fig leaf mottle-associated virus 1 (FLMaV-1), fig leaf mottle-associated virus 2 (FLMaV-2), fig mild mottle-associated virus (FMMaV), fig latent virus 1 (FLV-1), fig fleck-associated virus (FFkaV), and fig cryptic virus (FCV) using reverse transcription-polymerase chain reaction (RT-PCR) with specific primers. Three viruses were detected in mixed infections and showed positive results. FMV was detected with infection rate 49% followed by FLMaV-2 with infection rate 21.8% and FLMaV-1 with infection rate 10.9%, respectively, whereas all tested samples were negative for the other viruses. According to the sequence and phylogenetic analysis, the Egyptian FMV isolate was closely related to other FMV isolates, particularly the Argentina ones (Acc. No. KP796424), with 99% identity. While FLMaV-1 showed more than 98% identity with reference isolate FLMaV-1 (Acc. No. LN873219), on the other hand, the isolate of FLMaV-2 showed 100% identity with reference FLMaV-2 isolate (Acc. No. FJ473383) based on phylogenetic analysis. Because fig output in Egypt is expanding, our findings suggest that greater attention should be paid to improving the phytosanitary condition of fig trees in Egypt.